PENGARUH KOMPOSISI MEDIA TANAM ARANG SEKAM TERHADAP KARAKTER PERTUMBUHAN DAN HASIL BEBERAPA GENOTIP TANAMAN OKRA (Abelmoschus esculentus L.) - Hulya Hat taya; A Farid Hemon; Kisman *3 (CROP AGRO, Scientific Journal of Agronomy, 2019)
Okra (Abelmoschus esculentus L.) is one of the important vegetable crops. In its growth, okra plant is influenced by genetic and environmental factors especially planting media. This study aimed to determine the effect of composition of husk charcoal planting media on growth and yield characters of several okra genotypes. This study has been carried out in the greenhouse of Agriculture Faculty of Mataram University. The experiment was arranged in a factorial complete randomized design (CRD) consisting of two factor, namely the composition of planting media and genotype. The composition of planting media factor consist 0f 6 treatments while the genotype factor consist of 3 treatments. Every treatment combination was replicated three times so there were 54 plants (experimental unit). The research data were analized using analysis of variance at the 5% level of significant. Significant result were tested further with a honestly significant difference (HSD) method. Result of this study showed that interaction composition of planting media with genotype and the composition of planting media did not influence significantly all parameters. Genotype factor had affect significant on plant height 60 and 90 days after transplanting, flowering date, number of flower, number of flower become fruit, number of fruit suitable for comsumption, and length of fruit suitable for comsumption. The fastest growth among the genotype was Dompu genotype and the highest yield was Red genotype.